2016
DOI: 10.1080/13102818.2016.1232606
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of near-infrared transillumination in early caries diagnosis

Abstract: Early caries detection is essential for minimal intervention dentistry, since it could give the opportunity to reverse the process and eliminate or at least postpone the surgical treatment. The aim of the present study was to evaluate the effectiveness of near-infrared transillumination in early caries diagnosis for both occlusal and proximal lesions. Thirty-eight adult patients were included in the study. The results from the visual, radiological and near-infrared transillumination examination for proximal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…A recent clinical study comparing NIRTI to BWXRs that incorporated the excavation of lesions extending into dentin concluded that NIRTI has a diagnostic accuracy similar to BWXRs . Similarly, operative treatment in another recent clinical study confirmed the reliability of both radiographs and NIRTI as diagnostic tools for proximal caries lesions . A concern about validation via excavation, however, is that it could potentially neglect specificity (true negative), especially with enamel caries, since one of the major goals of these detection devices is early detection for minimal intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent clinical study comparing NIRTI to BWXRs that incorporated the excavation of lesions extending into dentin concluded that NIRTI has a diagnostic accuracy similar to BWXRs . Similarly, operative treatment in another recent clinical study confirmed the reliability of both radiographs and NIRTI as diagnostic tools for proximal caries lesions . A concern about validation via excavation, however, is that it could potentially neglect specificity (true negative), especially with enamel caries, since one of the major goals of these detection devices is early detection for minimal intervention.…”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, operative treatment in another recent clinical study confirmed the reliability of both radiographs and NIRTI as diagnostic tools for proximal caries lesions. 13 A concern about validation via excavation, however, is that it could potentially neglect specificity (true negative), especially with enamel caries, since one of the major goals of these detection devices is early detection for minimal interven- 7 Their results also showed that NIRTI has a higher sensitivity and specificity, but the study used a custom laboratory setup that did not specifically simulate intraoral conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Russotto, F. et al (20) who concluded that near-infrared transillumination performed significantly better than radiography as an interproximal caries detection tool. Also, Marinova-Takorova, M. et al (21) who concluded that nearinfrared transillumination is an effective method for diagnosis of lesions both involving only the enamel and involving the enamel and dentin for both occlusal and proximal caries lesions. Also, Simon, J. et al (22) who stated that near-infrared imaging was significantly more sensitive than radiography in detecting early carious lesions on both occlusal and interproximal surfaces, and Cirligeriu, L. et al (23) who found that there is a good correlation between near-infrared transillumination and radiography but the former proved more accurate compared to the later.…”
Section: Discussionmentioning
confidence: 99%
“…Schneiderman et al, Хэ-Вун и др. [18][19][20] установили, что в обнаружении окклюзионного кариеса метод DIFOTI с использованием устройства DIAGNOcam имеет более высокую чувствительность по сравнению с традиционными рентгенографическими методами и методом лазерной флуоресценции, кроме того, полученные результаты также наиболее тесно коррелируют с гистологическими результатами.…”
Section: методы трансиллюминацииunclassified